iMSC-mediated delivery of ACVR2B-Fc fusion protein reduces heterotopic ossification in a mouse model of fibrodysplasia ossificans progressiva - Pan Gao; Yoshiko Inada; Akitsu Hotta; Hidetoshi Sakurai; Makoto Ikeya (Stem Cell Research & Therapy, 2024)
Abstract Background Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disease caused by a gain-of-function mutation in ACVR1, which is a bone morphogenetic protein (BMP) type I receptor. Moreover, it causes progressive heterotopic ossification (HO) in connective tissues. Using FOP patient-derived induced pluripotent stem cells (FOP-iPSCs) and mouse models, we elucidated the underlying mechanisms of FOP pathogenesis and identified a candidate drug for FOP. Methods In the current study, healthy mesenchymal stem/stromal cells derived from iPSCs (iMSCs) expressing ACVR2B-Fc (iMSCACVR2B-Fc), which is a neutralizing receptobody, were constructed. Furthermore, patient-derived iMSCs and FOP mouse model (ACVR1R206H, female) were used to confirm the inhibitory function of ACVR2B-Fc fusion protein secreted by iMSCACVR2B-Fc on BMP signaling pathways and HO development, respectively. Results We found that secreted ACVR2B-Fc attenuated BMP signaling initiated by Activin-A and BMP-9 in both iMSCs and FOP-iMSCs in vitro. Transplantation of ACVR2B-Fc-expressing iMSCs reduced primary HO in a transgenic mouse model of FOP. Notably, a local injection of ACVR2B-Fc-expressing iMSCs and not an intraperitoneal injection improved the treadmill performance, suggesting compound effects of ACVR2B-Fc and iMSCs. Conclusions These results offer a new perspective for treating FOP through stem cell therapy.